Ultrasound Neurography in the Evaluation of Sciatic Nerve Injuries - Bilgici, Ayhan (The Society of Physical Therapy Science, 2013)
[Purpose] The aim of this clinical study was to investigate the benefits and the basic principles of ultrasonographic examination in the evaluation of sciatic nerve injuries. [Subjects and Methods] Patients with sciatic nerve injury were evaluated using a real-time utrasonographic examination. The capabilty of ultrasonography in terms of determination of the type and the localization of injury, the position of the proximal and distal nerve segments, the presence or absence of a neuroma, and perilesional scar tissue were evaluated in all cases. [Results] Ten cases with sciatic nerve injury were evaluated with real time sonography. Perilesional scar tissue formation was found in 4 (40%) cases. Two (20%) cases had stump neuroma diagnosed by sonographic examination. The capability of ultrasonographic examination was satisfactory for all evaluation parameters. [Conclusion] Ultrasonographic examination of sciatic nerve lesions may be used for the description of the degree of injury, determination of complete or incomplete nerve sectioning, the presence of hematoma and foreign body, the continuity of nerve, determination of nerve stumps, formation of perilesional scar tissue, and the presence of neuroma.